2021
DOI: 10.1080/19942060.2021.1961101
|View full text |Cite
|
Sign up to set email alerts
|

Different scenarios of glycerin conversion to combustible products and their effects on compression ignition engine as fuel additive: a review

Abstract: Different scenarios of glycerin conversion to combustible products and their effects on compression ignition engine as fuel additive: a review, Engineering Applications of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 160 publications
0
7
0
Order By: Relevance
“…However, glycerol is a versatile intermediate in waste valorization reactions such as oxidation, pyrolysis, hydrogenolysis, etherification, esterification, dehydration, polymerization and carboxylation. The purified glycerol is also commercially consumed in the pharmaceuticals, food and beverage industries [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, glycerol is a versatile intermediate in waste valorization reactions such as oxidation, pyrolysis, hydrogenolysis, etherification, esterification, dehydration, polymerization and carboxylation. The purified glycerol is also commercially consumed in the pharmaceuticals, food and beverage industries [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…6 The situation is not similar for crude glycerol as it has a low effective H/C ratio (0.67) and high density (d = 1.26 g cm −3 ), which not only affects its conversion but also leads to fast catalyst deactivation by coke formation. 17,18 These features limited the glycerol-to-aromatics (GTA) process, and therefore, the aromatic yield (<35C%) and p-X selectivity (<25%) achieved so far on ZSM-5-based catalysts are not satisfactory.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the processing of oxygen-containing bioderived feeds needs an additional step of dehydration or deoxygenation and hence demands special features of the catalysts to achieve sustainable activity for the effective production of aromatics even in the presence of water and other reaction environments. ZSM-5 is successfully employed for the methanol-to-aromatics (MTA) reaction due to its suitable acidity, three-dimensional (3D) pore structure, hydrophobicity (siliceous zeolite), high thermal stability, and higher aromatization activity . The situation is not similar for crude glycerol as it has a low effective H/C ratio (0.67) and high density ( d = 1.26 g cm –3 ), which not only affects its conversion but also leads to fast catalyst deactivation by coke formation. , These features limited the glycerol-to-aromatics (GTA) process, and therefore, the aromatic yield (<35C%) and p -X selectivity (<25%) achieved so far on ZSM-5-based catalysts are not satisfactory. Coprocessing of glycerol with alcohol (methanol) can increase the H/C eff ratio, which not only resolves the density issue of glycerol but also increases the alkyl-aromatics yield with an improved catalyst lifetime .…”
Section: Introductionmentioning
confidence: 99%
“…The process for conducting a systematic review of the documents is based on queries in the Scopus database integrated with PRISMA. The review methodology is based on earlier review techniques that were employed to build the state of the review on conventional neural networks in diverse applications [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. The PRISMA found that the two most popular classical machine learning techniques are support vector machines and long-short term memories The following Figure illustrates the schematic representation of the methodology which is planned in three levels.…”
Section: Introductionmentioning
confidence: 99%